Manufacturing Mennonites: Work and Religion in Post-War Manitoba - Marks, Lynne (Labour / Le Travail, 2015)
The article reviews the book, "Manufacturing Mennonites: Work and Religion in Post-War Manitoba," by Janis Thiessen.